How about Lexically Measuring Eastern European Literary Gypsylorism? Dual Othering and Linguistic Stereotyping of Roma Female Characters in the Modern Romanian Novel - David Morariu (Linguaculture)
This paper builds on Ken Lee’s concept of “Gypsylorism”, as a form of Said’s classical “Orientalism”, and argues for a particular case of Eastern European Gypsylorism in modern Romanian literature. More specifically, the paper examines the linguistic stereotyping of Roma female characters in five Romanian novels published in the first half of the 20th century. The lexical measurement of this form of Gypsylorism uncovers the influence of the Western pattern of orientalizing hypersexualized Roma characters, contrasted with lexical selections and discursive strategies that reflect an autochthonous perspective. This study advances the West-East dichotomy as a functional structure of overlapping the literary exoticization of Roma female characters—as a result of adapting the Western model of Roma othering—with an autochthonous perspective, rooted in the reality of Roma presence in Romanian society and in a reactionary discourse against the West. Consequently, the literary stereotypical portrayal of Roma female characters brings together the Western perspective of the mysterious and exotic femme fatale with an internal perspective on these characters, who long to leave their nomadic lifestyle behind and fall in love with Eastern European non-Roma male protagonists. In short, through the critique of this specific form of Gypsylorism, the paper intends to analyze the Romanian literary discourse and the “instrumentalization” of the fictional image of Roma.